PENGARUH METODE PEER EDUCATION TERHADAP PENGETAHUAN KESEHATAN REPRODUKSI PADA SISWI SMP DI PONDOK TA’MIRUL ISLAM SURAKARTA - Fikriyyah, Syarifatul; Dewi K, M. Nur; Astrika, Fresthy (Jurnal EDUNursing, 2017)
ABSTRACT Background: One of the problems of adolescent reproductive health is gaining knowledge and information whiteness is wrong and can not be accounted for. Peer Education is a learning method that uses a peer as a medium conveys information. This method is expected to take effect in conveying knowledge of whitish. The purpose of this study was to determine the effect of health education peer education on knowledge about whitish on second grade at Ta?mirul Islam Boarding school Surakarta.Method: The research was a quasy-experiment design with one group pretest-posttest. Sampling using total sampling as many as 69 students with questioner instrument. The data were analyzed using the Wilcoxon test.Result: The mean knowledge whitish pretest is 63.92 and posttest is 81.93. Wilcoxon test analysis result obtained significant value is 0.000Conclusion : There is the influence of the health education methods Peer Education to knowledge whitish in the second grade at Ta?mirul Islam Boarding school Surakarta Keyword : peer education, knowledge, whitish